The urban stage: reinventing interstitial space in Alexandra - Manala, Maria (My University, 2014)
This thesis seeks to explore the role of the performing arts in reconfiguring an unjust spatial history. By exploring the performing arts as a vehicle for creativity, freedom and a new consciousness within the city. Alexandra Township is still one of the impoverished settlements with very few public facilities, amenities and public space. The quality of its infrastructure is timeworn and does not meet all the needs of a society that is modernising. Finally there is now an increase in learners passing matric and wanting exposure to potential career options in the performing arts. This thesis will critically explore performance in the city - where the performer is seen as the self of all selves. It will also explore the meaning of public space in Alexandra and how the residents of Alexandra utilise public space for the purpose of performance. The idea of the building is to borrow from Alexandra where the building is seen as backstage and the township as the backdrop; A building that shapes and watches the urban life of Alexandra. This building speaks of an architecture which is connected with pockets of dignified public space. Fused with green spaces to create a theatre which becomes a green node for public space and the celebration of a performance culture found in Alexandra Township.
Keywords: City planning; Public spaces; Community development; Youth development; South Africa, Alexandra